Waiting-Line Auctions - Holt, Charles A.; Sherman, Roger (Journal of Political Economy, 1982)
If prizes are to be awarded simultaneously at a specified time on a first-come- first-served basis, then individuals who queue for them will choose different waiting times through their arrivals at the queue. This choice of arrival time at a queue is similar to the choice of a sealed tender in an auction. An equilibrium for this "waiting-line auction" is obtained here using methods for analyzing sealed-tender auctions. When individuals are risk neutral it is shown that several alternative waiting-line allocation procedures result in the same transactions cost associated with waiting in line.